A bibliometric analysis of the E-government studies with (UTAUT) - Amrouni, Khaled I. A.; Ruzaini, Abdullah Arshah (Universiti Malaysia Pahang, 2018)
this bibliometric study aims to present most important literature of the unified theory of acceptance and use of technology (UTAUT) used in the field of electronic government (e-government). This study relied on the Web of Science Database (WoS) which index an elite of publications with ISI standard only. WoS was used to inspect the literature which utilized the UTAUT theory with in the subject of e-government, 41 publications were found and analyzed to extract the bibliometric parameters which are as following; Citation report, Production report and Methodological haracteristics report. The study is to be considered as a milestone within the mention fields, where it provide help and guidance to new scholar, saving their effort and time by summarizing and reporting the most important (Cited) articles, authors, Journals, and countries that are publishing in the field of e-government using UTAUT as a research theory, as well as the most productive authors, Journals, and academic institutions. In addition to an in-depth report for the Methodological characteristics of the studied publications, to identify gaps and recommendations for further studies.